Interação entre a qualidade de resíduos culturais e a textura do solo com a dinâmica do carbono - Schmatz, Raquel (2016)
The chemical quality of crop residues is considered the primary driver of the dynamics of carbon and stabilization of soil carbon (C) from the crop residues (C-new) depend on the soil texture. The aim of this study was to evaluate the quality of crop residues and soil texture on the decomposition and the quantity of C-new in the soil the short term. The incubation experiment was conducted for 180 days in Ultisol and Oxisol soils with contrasting texture and three crop residues enriched with 13C, wheat (Triticum aestivum), pea (Pisum sativum L.) and vetch (Vicia sativa L.) under conditions controlled temperature and humidity in the LABCEN of the Department of Soil Science at UFSM. The experiment was conducted in a completely randomized design with three replications and eight treatments: T1- Soil Ultisol (SU); T2- Soil Oxisol (SO); T3 - SU + straw wheat; T4 SU + straw pea; T5- SU + straw vetch; T6- SO + straw wheat; T7- SO + straw pea; and T8- SO + straw vetch. The evaluation of the mineralization of C was carried out through the release of CO2 and 13C was evaluated by measuring 13CO2 released during decomposition of crop residues, always in the same bottles. Six evaluations were released to determine the quantity of C and 13 C remaining in the crop residues and the soil, and recovery of 13C. The quality of crop residues and the soil texture affect the mineralization of C of crop residues. The early stage of decomposition, highest mineralization the C was found with the residue vetch, and at the end of the experiment, the residues of wheat had the highest quantity of C mineralized and in the sandy soil. The quantity C-new of soil from the shoots plants, of wheat, pea and vetch is not affected by the quality of crop residues and the soil texture.